PERBEDAAN GANGGUAN HOMEOSTASIS PADA PENDERITA DEMAM BERDARAH DENGUE TANPA SYOK DAN SSD (SINDROM SYOK DENGUE) - - Pujiati (Majalah Ilmiah Sultan Agung, 2009)
Coagulation disorders in DHF represent the main pathogenesis which led to bleeding manifestation. Coagulation disorders and fibrinolysis have been attributed to the occurrence of DIC with bleeding manifestation. which is a homeostasis disorder that occurred in DHF. This study was conducted to evaluate the difference of kinetic of homeostasis disorder in DSS and Non DSS. An explorative observational research was conducted to 97 patients with DHF, consisting of 47 DSS and 50 Non DSS. The patients, age were 3- 14 years old, who admitted to Pediatric Ward or Pediatric Intensive Care Unit (PICU) Dr. Kariadi Hospital from February 2011 until February 2002. Diagnosis of DHF was based on criteria of WHO 1999. Parameter for coagulation disorders: PT, PTT, fibrinogen were examined on day 0 (on admission), 1,2, and 7. Data were analyzed using independent t-test, Mann-Whitney test and X2 test using SPSS 11.5 for window. The result is considered significant if p < 0.05. The caring periods, hemoglobin, hematokrit, and leucocytes were significantly higher in DSS compared to non DSS (p < 0.05). Homeostasic disorders in DHF may occur from first day of admission or on the third day of fever and gradually become normal on seventh day. Hemeostatic disorders in DSS are more severe compared to non DSSKeyword: Dengue hemorrhagic fever (DHF), Dengue shock syndrome (DSS), homeostatic disorder